The Use of Visual Learning Media in The Development Optimization of Children with Mild Mental Retardation - Viny Anggradini Puspitaloka; Khamim Zarkasih Putro; Tri Rukmana; Fifi Elvia (JOYCED: Journal of Early Childhood Education, 2022)
Children with mild mental retardation are different from normal children in general. Mild mentally retarded children have learning difficulties evident in the academic field. Therefore, to teach learning materials to children with mild mental retardation, teachers need to provide learning media. One of them is visual media. So this study aims to analyze the use of visual learning media in optimizing all aspects of the development of mild mentally retarded children. This research uses the literature review method with thematic structure data collection techniques and Critical appraisal analysis techniques. In this study, all results obtained in the reviewed literature showed that visual learning media significantly influenced the development of children with mild mental retardation. The visual learning media used in the research that has been carried out are blocks, counting boards, drawing cards, word walls, busy books, and picture crosswords. This is undoubtedly very helpful for teachers in the learning process because visual media can contain various learning materials to increase the interest and enthusiasm for learning of children with mild mental retardation.